Historical institutionalist analysis of low-carbon energy transition in the Philippines and Indonesia - Sembiring, Margareth Yasintha (Nanyang Technological University, 2024)
This dissertation seeks to examine why developing countries still take up low-carbon energy transition agenda despite financial and technological hurdles, and why some of them implement the agenda faster than others. This study argues that despite financial and technological hurdles, a developing country still decides to implement low-carbon energy transition agenda because the State positively evaluates the benefits of renewable energy development for the country’s economic and energy security interests. The pace of progress is subsequently influenced by State involvement in the energy sector, its interests and priorities, and its relation with the private sector, which are formed through historical sequences and processes over time.